South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
South Africa's macroeconomic policies face a complicated task of balancing between supporting domestic demand and maintaining stability. The Selected Issues paper for South Africa discusses economic development and policies. Although the opening output gap and declining employment do call for countercyclical fiscal and monetary policy easing, policymakers should also be mindful of the effects of such policies on external and internal macroeconomic stability. The combined package of monetary and fiscal policies has considerable effects on growth and employment.